The History of Qur’anic Exegesis during the Abbasid Period: From Codification to Philosophical Exegesis - M. Sofiyulloh; Muhammad Ali Murtadlo (Jurnal Semiotika Quran, 2026)
This article aims to discuss the historical development of Qur’anic exegesis during the Abbasid dynasty, namely from 750 CE to 1258 CE. The discussion focuses on the history of the Abbasid dynasty, the development and codification of exegesis, the works and exegetes, as well as the dominant philosophical pattern of exegesis. This study employs a qualitative method and a type of library research that focuses on the study of texts and ideas concerning the dynamics of the development of Qur’anic exegesis and the emergence of philosophical exegesis during the Abbasid era. The results of this study indicate that the codification of exegesis writing, which began from the time of the Prophet until the medieval period, gave rise to a new method of interpretation, namely bi al-ra’y. This form of exegesis is based on previous  interpretations  derived  from  the  Prophet’s  hadith,  the  sayings  of the companions, and the tabi‘in. Regarding philosophical exegesis, the scientific confrontation that occurs within it departs from the classification of interpretive patterns into two, namely bi al-ma’thūr and bi al-ra’y (bi al-ijtihād), with philosophical exegesis included in this category. Meanwhile, the difference between the two lies in the presence or absence of a foundation in historical and linguistic realities within the text of the Qur’an as the basis of interpretation. This article contributes to enriching the treasury of Islamic thought by affirming that philosophical exegesis, although it invites pros and cons, plays an important role as a bridge between rationality and spirituality, while also showing that the Qur’an can be understood as an open text that encourages the human intellect to continuously explore new wisdom in line with the development of science and technology. In addition, the dialectic between revelation and reason during the Abbasid period demonstrates the strength of the Islamic intellectual tradition, so Muslims need to be open and realize that faith must be accompanied by deep understanding.